Litter and soil properties are not altered by invasive deer browsing in northern Patagonia forests. - Relva, Maria Andrea (2014)
It is largely accepted that large mammalian herbivores can indirectly influence ecosystem properties by changing the quantity and quality of litter inputs to soil through selective browsing on plant communities. However, idiosyncratic effects (positive, neutral and negative) have been found for different vegetation types, herbivory and soil properties. In this study we tested whether browsing by exotic deer introduced into Patagonian forests 90 years ago alters physical, chemical and biological soil properties and litter quantity and quality. As in many terrestrial ecosystems, N is the main nutrient that limits plant growth in Patagonia. Consequently, any disturbance that alters the N cycle, such as changes in the type or intensity of herbivory, is expected to affect these forest ecosystems. We compared soil and total litter from inside and outside five 7-yr old exclosures located on Isla Victoria, Parque Nacional Nahuel Huapi, Argentina. Despite introduced deer has significantly affected the composition, abundance and structure of the understory vegetation, we found no differences between browsed and unbrowsed areas in the physical (bulk density, moisture), chemical (pH, base cations, organic C and total N) and biological (potential microbial respiration and net N mineralization) soil properties. This could be attributable to the high capacity of volcanic soils to stabilize organic matter, buffering disturbance-induced changes. However, the quantity and quality (C, N and C/N ratio) of total litter were also not different between browsed and unbrowsed areas. Although non-significant differences were found between treatments in both compartments, litter and soil, most variables showed a slight trend toward higher values in unbrowsed areas. This suggests that 7 years of browsing exclusion would be not enough to detect changes induced by browsing, particularly in highly stable volcanic soils.